Estudio de factibilidad para la apertura de la sucursal de la cevichería el gordo lucho 2, cantón El Empalme, Año 2014 - Santana Romero, Juan Carlos (2015)
The city of El Empalme in recent years has shown a significant economic and population development, has a privileged location that allows you to communicate strategically with the rest of the country, This feasibility study for the opening of the branch cevichería "the big fight 2", it has raised according to the technical conditions and requirements of products to offer. Further study on the economic investment required for the project are detailed, and the feasibility of it is demonstrated, finally the financial evaluation is performed by applying financial indicators such as NPV, IRR, RBC. Thus the need to implement a new branch of cevichería "El Gordo Lucho" that meets the segment of university students, office workers, and families who can not return home to feed was identified. According to the results of market research, respondents breakfast and / or lunch between 08:30 and 14:30; showing willing to pay an average of $ 5 per plate. Most prefer selected, excellent and healthy food where they can find food to the highest quality standards and are accessible to everyone. The project albeit indirectly compete with companies of restaurants and cafes. All these establishments offer their products at an average price of 3 to $ 6….